Growth and Yield Response of Pagoda Mustard to Nitrogen Fertilizer and Biostimulant Application on Podzolic Soil - Feneranda Anggraeny; Evi Gusmayanti; Cico Jhon Karunia Simamora (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Pagoda mustard is a new type of vegetable in Indonesia with high economic potential, but its cultivation is still limited. One of the challenges in its development is the use of Red-Yellow Podzolic soil, which is characterized by acidic pH, low organic matter, and limited nutrient availability, all of which can hinder plant growth. The use of biostimulants and balanced fertilization in cultivated plants can provide optimal growth and yield. The research was carried out in West Kalimantan, for two months from May to July 2024, using a Factorial Completely Randomized Design with two factors: biostimulants application (without and with biostimulants) and nitrogen fertilizer application at three levels (100, 200, and 300 kg.ha-1). The results indicate that the combined application of biostimulants and nitrogen fertilizer did not show interactions for any observed variables. However, a single treatment of biostimulants could increase the number of leaves, leaf area index, root volume, dry weight, and amino acid levels of pagoda mustard plants. Nitrogen fertilizer at 100 kg.ha-1 was found to be an efficient treatment to increase the growth and yield.